CooA, a CO-sensing transcription factor from Rhodospirillum rubrum, is a CO-binding heme protein - Shelver, Daniel (The National Academy of Sciences of the USA, 1997)
Biological sensing of small molecules such as NO, O(2), and CO is an important area of research; however, little is know about how CO is sensed biologically. The photosynthetic bacterium Rhodospirillum rubrum responds to CO by activating transcription of two operons that encode a CO-oxidizing system. A protein, CooA, has been identified as necessary for this response. CooA is a member of a family of transcriptional regulators similar to the cAMP receptor protein and fumavate nitrate reduction from Escherichia coli. In this study we report the purification of wild-type CooA from its native organism, R. rubrum, to greater than 95% purity. The purified protein is active in sequence-specific DNA binding in the presence of CO, but not in the absence of CO. Gel filtration experiments reveal the protein to be a dimer in the absence of CO. Purified CooA contains 1.6 mol heme per mol of dimer. Upon interacting with CO, the electronic spectrum of CooA is perturbed, indicating the direct binding of CO to the heme of CooA. A hypothesis for the mechanism of the protein’s response to CO is proposed.